Student Perceptions of the Role of Microteaching Courses as Preparation for Implementing Field Experience Practices - Rizqi Rahmania Nurwahidah; Yuli Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Microteaching is widely implemented as a preparatory course prior to Field Experience Practice (FEP); however, its effectiveness in representing the complexity of authentic classroom instruction remains contested. This study aims to analyze students’ perceptions of microteaching as preparation for FEP and examine the relationship between students’ perceptions and their academic achievement in the microteaching course. A convergent mixed-methods design was employed involving 35 undergraduate students enrolled in a Japanese Language Education program. Data were collected through an online questionnaire consisting of students’ perceptions of microteaching and documentation of final course grades. Quantitative data were analyzed using descriptive statistics, normality testing, and correlation analysis, while qualitative data were analyzed through thematic analysis. The findings revealed that students generally perceived microteaching positively, particularly in enhancing self-confidence, teaching readiness, and adaptability to student characteristics. Nevertheless, no significant relationship was identified between students’ perceptions and their academic achievement in microteaching. Qualitative findings further indicated a discrepancy between simulated teaching practices and actual classroom conditions, alongside the need to strengthen reflective, contextual, and collaborative dimensions within microteaching instruction. The study concludes that microteaching contributes more substantially to students’ affective and pedagogical readiness than to academic performance alone. The findings imply the importance of developing more authentic microteaching models to support the development of comprehensive pedagogical competence.